Environmental impact of textiles : production, processes and protection - Slater, Keith (Woodhead publishing in textiles, 2003)
This comprehensive book examines the effects that all phases of textile production and use have on the environment, from growing or making fibres to discarding a product after its useful life has ended. It looks at the physical environment affected by these processes, including resource depletion, pollution and energy use and the biological environment, by considering what happens as a result of manufacture. It also considers the degradation suffered by textile materials within the environment whether by air pollution, wind, water and other agents. The most recent solutions adopted by the indu.